THE IMPACT OF ORGANIZATIONAL CULTURE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE: THE MEDIATING ROLE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN COMMUNITY-BASED ECOTOURISM - Krisna Veda Aryaputra; Andini Risfandini; Tanto G. Sumarsono; Sindi Prati Minanda (Adisam Publisher, 2025)
This study explores the interplay between organizational culture, work motivation, and organizational citizenship behavior (OCB) in shaping employee performance within community-based ecotourism at Clungup Mangrove Conservation (CMC). The findings highlight that a strong, value-aligned organizational culture fosters voluntary and pro-conservation behaviors among employees. Motivation acts as a crucial mediating factor, translating cultural values into tangible actions supporting conservation and service excellence. OCB serves as a vital bridge, enabling employees to go beyond formal roles, thereby enhancing both performance and sustainability outcomes. The research underscores the importance of holistic strategies that integrate cultural reinforcement, motivational enhancement, and encouragement of discretionary behaviors to achieve sustainable ecotourism performance. These insights contribute to the theoretical and practical understanding of human resource management in conservation-oriented organizations and emphasize the significance of cultivating a shared organizational ethos to promote behavioral commitment and community engagement.